The Work Ethic, Self-Efficacy and Performance of Civil Servants at the Public Works and Spatial Planning Service - Elpi Yanti (Jurnal Manajemen Sains dan Organisasi, 2023)
Objective - This research aims to determine the influence of work ethic and self-efficacy on the performance of civil servants in the Public Works and Spatial Planning Service Design/Methodology/Approach - The analytical method used in this research is quantitative. The population and sample in this study were all Civil Servants of the Public Works and Spatial Planning Department of Gunung Mas Regency, totaling 69 people using census techniques. The analytical method used in this research is Partial Least Square (PLS) with the SmartPLS 4.0.9.3 analysis tool. Research findings - The results of this research show that work ethic has a positive and significant effect on performance and self-efficacy has a positive and significant effect on the performance of employees of the Gunung Mas Regency Public Works and Spatial Planning Service. Conclusions and Implications – Work ethic and self-efficacy have a positive influence on civil servant performance. The Public Works and Spatial Planning Department can improve the work ethic and self-efficacy of employees if they want to improve the performance of civil servants.